(untitled) (Fiep Bulletin - online, 2015)
The hygienic practices must be maintained in any kind of establishment, handlers and environments must abide by ANVISA regulation. From the analysis of the charts there is a great number of handlers, following the criteria of the Health Surveillance Agency, which can be damaging to consumers due to the lack of hygiene in the preparation of food and inefficient site cleaning. We aim to qualify the importance of food handlers and environmental hygiene. Objective: Verify the hygienic sanitary practices of the handlers and environment where food is manipulated, co-relating Law demanded care with the observed. We are able then to evaluate the profile of the handlers, along with their work environment. Methods: It’s a transversal research with an observational study, in which factor and effect were visualized at the moment of data colleting, descriptive and quantitatively. A specific food commercial establishment, based on the handled foods public health. Materials: Check list for the data colleting, must abide by regulation, and proven by photography. Results: It was observed that 60% of the food handlers wear improper attire; only 40% wear hairnets, 49% wear tennis shoes and varied types of props. Referring to the handling area 13% of the diners were completely clean; cleaning products were found in 78%; wood or cardboard was found in 38%; a metal or steel brush was found in 37%; dish rags were found in 80%; torn, pierced and dirty packages were found in 55%. Only 72% had their own ventilation system; scrap, garbage and animals were found in 66%; clean surface were found in 67%; proper lighting was found in 44%; proper wiring installation was found in 71%. Lidded sanitary facilities in 80%; trash can with pedal and lid was found in 77%; sink with liquid soap was found in 53% and disposable towels were found in 62%.Conclusion: The results suggest that the snack bars, as well as the handlers, aren’t in accordance with current legislation.